Acute Renal Failure in Association with Community-Acquired Clostridium difficile Infection and McKittrick-Wheelock Syndrome - Robert M. Learney; Paul Ziprin; Pauline A. Swift; Omar D. Faiz (Case Reports in Gastroenterology, 2011)
We report the case of a 65-year-old Caucasian woman who experienced two separate episodes of acute renal failure within an 18-month period, both requiring emergency admission and complicated treatment. Each episode was precipitated by hypovolaemia from intestinal fluid losses, but from two rare and independent pathologies. Her first admission was attributed to community-acquired Clostridium difficile-associated diarrhoea (CDAD) and was treated in the intensive therapy unit. She returned 18 months later with volume depletion and electrolyte disturbances, but on this occasion a giant hypersecretory villous adenoma of the rectum (McKittrick-Wheelock syndrome) was diagnosed following initial abnormal findings on digital rectal examination by a junior physician. Unlike hospital-acquired C. difficile, community-acquired infection is not common, although increasing numbers are being reported. Whilst community-acquired CDAD can be severe, it rarely causes acute renal failure. This case report highlights the pathological mechanisms whereby C. difficile toxin and hypersecretory villous adenoma of the rectum can predispose to acute renal failure, as well as the values of thorough clinical examination in the emergency room, and early communication with intensivist colleagues in dire situations.